Characterization and modeling of negative bias temperature instability in P-MOSFETs - Yang, Jianbo (2010)
This thesis is concerned with the study of negative bias temperature instability (NBTI) in p-MOSFETs. A simple characterization method based on the single-point measurement of the saturated drain current is first proposed to minimize the unwanted recovery effect during the NBTI measurement. A study on the NBTI recovery is also conducted as it may help predict the actual device lifetime with a better accuracy and may improve the understanding of the NBTI mechanism also. An analytical reaction-diffusion (R-D) model within the framework of the standard R-D model is proposed to describe the NBTI process in a wide time scale covering the three regimes of reaction, transition and diffusion. An analytical reaction-dispersive-diffusion (RDD) model is further developed by incorporating the dispersive transport nature of the diffusion into the R-D model. The RDD model can well explain the nitrogen-enhanced NBTI effect. It can also well describe the NBTI degradation including its dependence on the stress time, stress temperature and interfacial nitrogen concentration and its power-law behaviors as well. This in turn gives an insight into the roles of the hydrogen dispersive diffusion in the NBTI process. First-principles calculations are also carried out to examine the effects of nitrogen on NBTI in terms of the influence of nitrogen on the NBTI reaction energy, electro-negativity and atomic charge distribution. Impacts of various advanced process technologies, e.g., stress proximity technique, 45°-rotated silicon substrate, laser spike annealing, on the NBTI are investigated. NBTI degradation behaviors of 65/45nm high-performance p-MOSFETs with ultrathin gate oxide, including the impact of gate oxide process and the geometry dependence are studied.